2007
DOI: 10.1128/jvi.00055-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasmid DNA Vaccine Design and In Vivo Electroporation on the Resulting Vaccine-Specific Immune Responses in Rhesus Macaques

Abstract: Since human immunodeficiency virus (HIV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
105
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(121 citation statements)
references
References 81 publications
12
105
1
3
Order By: Relevance
“…In addition, electroporation induced a broader repertoire of cellular immune responses against subdominant antigens including preS, Core, and Pol, even though the magnitude was not as great as with the S antigen. These encouraging data are consistent with previous reports regarding the potency of EP-based plasmid DNA vaccination in large animals, including monkeys (Luxembourge et al, 2005;Otten et al, 2006;Luckay et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, electroporation induced a broader repertoire of cellular immune responses against subdominant antigens including preS, Core, and Pol, even though the magnitude was not as great as with the S antigen. These encouraging data are consistent with previous reports regarding the potency of EP-based plasmid DNA vaccination in large animals, including monkeys (Luxembourge et al, 2005;Otten et al, 2006;Luckay et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that the magnitude of immune responses induced in primates is lower than that in small animals, and the quantity of DNA required for the effective immunization of primates is significantly higher (mg vs μg) (Aihara et al, 1998;Selby et al, 2000). Electroporation (EP) resolves this problem via the introduction of plasmid DNA into the cells to a degree adequate for optimal immune response at low dosages (Luckay et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…3 Extensive investigation by many groups over the past decade has enabled vast improvements in the technology and transduction efficiency, 2 such that it has now been successfully used in pre-clinical and clinical trials for the delivery of therapeutic plasmids 4 and DNA vaccines. 5,6 However, two unresolved aspects of ET are the underlying nature of any tissue response to the ET process as a measure of safety and/or any immunological response induced by the procedure and/or nucleic acid itself. With regard to safety, the continued evolution of new ET conditions and non-viral delivery agents towards the clinic necessitates a firm understanding of tissue responses and the development of appropriate tools for assessing and minimising potential adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most striking advances for plasmid delivery in vivo the most potent has been that of electroporation (EP). Studies have showed that EP has been a feasible method for DNA vaccine delivery to enhance both cellular and humoral responses (23,24).…”
mentioning
confidence: 99%